The ministry of Social Welfare during Francisco Manrique’s administration. The role of social policy in the last years of the Revolución Argentina (1970-1973) (Quinto Sol, 2017)
The present paper examines the policies carried out by Minister of Social Welfare, Francisco Manrique throughout the de facto presidencies  of Generals Roberto Levingston (1970-1971) and Alejandro Lanusse (1971-1973). I argue that the social policies and strategies implemented by Manrique aimed at building the consensus needed in view of the government’s forthcoming political openness, and at the same time were leaded by his veiled intention of launching his presidential candidacy for the elections that would take place in 1973.
Keywords: Recent history; Revolución Argentina; Social policies; Dictatorship; Gran Acuerdo Nacional